Penyalahgunaan Fungsi Tanah Kas Desa di Kecamatan Banguntapan Kabupaten Bantul Daerah Istimewa Yogyakarta - Fattahilah Fahmi (Universitas Islam Indonesia, 2016)
AbstractThis study discusses the misuse of land in the District Rural village treasury Banguntapan Bantul Yogyakarta. This type of research used in this research is the empirical jurisdiction. The study concluded that the abuse of cash land Banguntapan village in the district of Bantul Regency involve various stakeholders ranging from the government, the communities, and also the local notary. Cash Land Village is one of the village valuable asset because it serves as the village's largest revenue source then sebaikanya existence should be safeguarded. The village government must act decisively against the survival of the village treasury land and provide sanctions against infringing on the case. So that the wealth of the village could be felt by all people, especially villagers do not violate regulations.Keywords: Soil village treasury, Notary, Bantul.